Between two photographs: 1844’s The Haystack and 2017’s The Charcoal Kiln / Mohammad Firdaus Azman ... [et al.] - Azman, Mohammad Firdaus; Padil, Md Nagib; Ibrahim, Khairul Anuar; Mohd Rafee, Mohd Radzuan (2023)
On his country estate at Lacock Abbey in Wiltshire in April 1844, William Henry Fox Talbot (Fig.1) set up a camera filled with light sensitive paper and photographed a haystack. A hay knife can be seen high in the stack to the left of the leaning ladder, and the blocks are being chopped from the top down in this photograph. Careful thatching and an undercut design shield the precious crop from precipitation. You can make out what seems like a barn with a thatched roof behind the stack